2020
DOI: 10.3389/fendo.2020.00099
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Perspectives on the Developing Skeleton and Implications for Lifelong Health

Abstract: Osteoporosis is a significant cause of morbidity and mortality in contemporary populations. This common disease of aging results from a state of bone fragility that occurs with low bone mass and loss of bone quality. Osteoporosis is thought to have origins in childhood. During growth and development, there are rapid gains in bone dimensions, mass, and strength. Peak bone mass is attained in young adulthood, well after the cessation of linear growth, and is a major determinant of osteoporosis later in life. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 119 publications
(131 reference statements)
4
37
0
1
Order By: Relevance
“…Fragility fractures resulting from reduced bone strength are relatively rare in bioarchaeological studies (Agarwal 2008;Agarwal and Grynpas 1996), even among the elderly, leading some to conclude that osteoporosis was rare or absent in past populations (but see (Curate et al 2010;Dequeker et al 1997)). This and the fact that agespecific osteoporotic fracture incidence rates appear to be increasing over time in Western populations (Cooper et al 2011) lends support to the notion that osteoporosis is a modern disease (Kralick and Zemel 2020;Lieberman 2013). On the other hand, few if any bioarchaeologists systematically study thoracic vertebral compression fractures.…”
Section: Discussionmentioning
confidence: 87%
“…Fragility fractures resulting from reduced bone strength are relatively rare in bioarchaeological studies (Agarwal 2008;Agarwal and Grynpas 1996), even among the elderly, leading some to conclude that osteoporosis was rare or absent in past populations (but see (Curate et al 2010;Dequeker et al 1997)). This and the fact that agespecific osteoporotic fracture incidence rates appear to be increasing over time in Western populations (Cooper et al 2011) lends support to the notion that osteoporosis is a modern disease (Kralick and Zemel 2020;Lieberman 2013). On the other hand, few if any bioarchaeologists systematically study thoracic vertebral compression fractures.…”
Section: Discussionmentioning
confidence: 87%
“…This and the fact that age-specific osteoporotic fracture incidence rates appear to be increasing over time in Western populations ( Cooper et al, 2011 ) lends support to the notion that osteoporosis is a ‘disease of modernity’ (cf. Kralick and Zemel, 2020 ; Lieberman, 2013 ). However, few if any bio-archaeologists systematically study thoracic vertebral compression fractures, and a paucity of observed fragility fractures in the archaeological record is partly due to biased preservation of skeletal remains.…”
Section: Discussionmentioning
confidence: 99%
“…Peak bone mass has been proposed as the single most important factor that can be intervened to prevent osteoporosis later in life [15]. This is expected, as peak BMD explains considerably more variance than bone loss, for any BMD measurement during late adulthood [15].…”
Section: Fracture Risk Across the Lifespanmentioning
confidence: 98%
“…Peak bone mass has been proposed as the single most important factor that can be intervened to prevent osteoporosis later in life [15]. This is expected, as peak BMD explains considerably more variance than bone loss, for any BMD measurement during late adulthood [15]. A simulation study predicted that an increase of 10% in the magnitude of peak bone mass can delay the onset of osteoporosis by 13 years [16].…”
Section: Fracture Risk Across the Lifespanmentioning
confidence: 99%